MGA and growth promotants administered to beef feedlot heifers have no effect on subsequent oocyte quality or in vitro embryo production - Miller, N.; Grieger, David M.; Fike, Karol E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
Beef feedlot heifers have the potential to serve as viable donors of oocytes post-slaughter for in vitro embryo production. Oocyte quality is a critical factor affecting the success of in vitro embryo production and can be influenced by factors such as age and reproductive status, ovarian follicle size, and nutritional status of the donor female. In a conventional feedlot setting, heifers are typically administered steroid-based growth promotants and fed melengestrol acetate (MGA) for suppression of estrus, which increases circulating concentrations of reproductive steroids, particularly estradiol. The effects of these management practices on oocyte quality and numbers are unknown. The purpose of this study was to compare oocytes harvested from traditionally managed beef feedlot heifers implanted with growth promotants and fed MGA with oocytes from heifers given neither MGA nor growth promotants, and to evaluate potential effects of these feedlot management practices on early embryo development.
Keywords: Beef; MGA; Heifers; Oocyte quality; In vitro embryo